Simulated Annealing Algorithm for Solving Modified VRPTW Problem in Time-Dependent Networks: A Case Study - Wojciech KULAS; Zbigniew TARAPATA (Communications of International Proceedings, 2021)
The paper describes modifications to the simulated annealing algorithm for solving modified Vehicle Routing Problem with Time Windows problem. Our modification of the classic VRPTW include many warehouses, a heterogeneous fleet, stochastic time-dependent travel times (stochastic time-dependent network) and an extensive cost function. The described results are the outcome of a research project, the results of which are currently being implemented in logistics companies. A review of the literature related to the solved problem was made, the idea of the simulated annealing algorithm was described, followed by its modifications and their influence on the search for a solution, a group of calibration parameters was presented, which are used to influence the way the algorithm behaves, the obtained results of the modified algorithm on the so-called benchmarks were described. Finally, some conclusions and recommendations were made.
Keywords: VRPTW problem; simulated annealing; calibration parameters; time-dependent networks; VRPTW benchmarks.